Drifting in the oceans: Isarachnanthus nocturnus (Cnidaria, Ceriantharia, Arachnactidae), an anthozoan with an extended planktonic stage - Stampar, Sérgio N. [UNESP]; Morandini, André C.; Branco, Laura C.; da Silveira, Fábio Lang; Migotto, Alvaro E. (Springer Nature, 2015)
The life cycles of many marine taxa are still unknown, especially those species with indirect development and long-lived larval stages. Life cycles of cnidarians are relatively well known for most groups except Ceriantharia. This taxon presents taxonomic problems stemming from the lack of association between planktonic larval forms, often described as distinct species, with the corresponding adult benthic stages. Our study focused on the development of larvae with peculiar external morphology that could be linked to a described species established from adult specimens. Through cultivation of these larvae to juveniles with adult-like morphology and also with the use of DNA barcoding, it was possible to link the stages observed to a known species, Isarachnanthus nocturnus. Based on life span of the larva in the plankton (63–118 days), the larvae could potentially drift for about 2000–4000 km along the coast. Because rearing larvae in the laboratory may be complex and time-consuming and also because morphological data may have limited distinguishing power for specific identification of larvae collected in the field, we suggest and discuss the use of DNA barcoding as a tool to connect life stages of species of cerianthids and invertebrates in general.